Crónicas dos Motins - Granjo, Paulo (Anropocoiso - Blog de Paulo Granjo, 2008)
Mensagens correspondentes à consulta "Crónicas dos Motins".
Keywords: *non-public; G - Mozambique / Moçambique; L - portuguese / português; conflict / conflito

Mapeamento das Mudanças Alcançadas: Construindo Aprendizagem e Reflexão em Programas de Desenvolvimento - Earl, Sarah; Carden, Fred; Smutylo, Terry (FURG (pt) and IDRC (en), 2008)
More and more, development organizations are under pressure to demonstrate that their programs result in significant and lasting changes in the well-being of their intended beneficiaries. However, such "impacts" are often the product of a confluence of events for which no single agency or group of agencies can realistically claim full credit. As a result, assessing development impacts is problematic, yet many organizations continue to struggle to measure results far beyond the reach of their programs. Outcome Mapping recognizes that development is essentially about people relating to each other and their environment. The originality of this approach lies in its shift away from assessing the products of a program to focus on changes in behaviour, relationships, actions, and activities in the people, groups, and organizations it works with directly. In doing so, Outcome Mapping debunks many of the myths about measuring impact. It will help a program be specific about the actors it targets, the changes it expects to see, and the strategies it employs and, as a result, be more effective in terms of the results it achieves. This publication explains the various steps in the outcome mapping approach and provides detailed information on workshop design and facilitation. It includes numerous worksheets and examples.
Keywords: *tagged; L - portuguese / português; M - evaluation / avaliação; M - methodology / metodologia